Antimitochondrial antibody heterogeneity and the xenobiotic etiology of primary biliary cirrhosis1. Issue 4 (29th January 2013) - Chen, Richy C.Y.; Naiyanetr, Phornnop; Shu, Shang‐An; Wang, Jinjun; Yang, Guo‐Xiang; Kenny, Thomas P.; Guggenheim, Kathryn C.; Butler, Jeffrey D.; Bowlus, Christopher; Tao, Mi‐Hua; Kurth, Mark J.; Ansari, Aftab A.; et al.
Abstract Antimitochondrial antibodies (AMAs) directed against the lipoyl domain of the E2 subunit of pyruvate dehydrogenase (PDC‐E2) are detected in 95% of patients with primary biliary cirrhosis (PBC) and are present before the onset of clinical disease. The recent demonstration that AMAs recognize xenobiotic modified PDC‐E2 with higher titers than native PDC‐E2 raises the possibility that the earliest events involved in loss of tolerance are related to xenobiotic modification. We hypothesized that reactivity to such xenobiotics would be predominantly immunoglobulin M (IgM) and using sera from a large cohort of PBC patients and controls (n = 516), we examined in detail sera reactivity against either 6, 8‐bis(acetylthio) octanoic acid (SAc)‐conjugated bovine serum albumin (BSA), recombinant PDC‐E2 (rPDC‐E2) or BSA alone. Further, we also defined the relative specificity to the SAc moiety using inhibition enzyme‐linked immunosorbent assay (ELISA); SAc conjugate and rPDC‐E2‐specific affinity‐purified antibodies were also examined for antigen specificity, isotype, and crossreactivity. Reactivity to SAc conjugates is predominantly IgM; such reactivity reflects a footprint of previous xenobiotic exposure. Indeed, this observation is supported by both direct binding, crossreactivity, and inhibition studies. In both early and late‐stage PBC, the predominant Ig isotype to SAc is IgM, with titers higher with advanced stage disease. We also note that there was a higher level of IgM reactivity to SAc than to rPDC‐E2 in early‐stage versus late‐stage PBC. Interestingly, this finding is particularly significant in light of the structural similarity between SAc and the reduced form of lipoic acid, a step which is similar to the normal physiological oxidation of lipoic acid. Conclusion: Specific modifications of the disulfide bond within the lipoic‐acid‐conjugated PDC‐E2 moiety, i.e., by an electrophilic agent renders PDC‐E2 immunogenic in a genetically susceptible host. (HEPATOLOGY 2013)